Machinability Study of Cast Iron in Small and Medium Enterprise - Haris Nasution, Abdul; Rasyid Harahap, Muksin; Napid, Suhardi; Rafiq Yanhar, Muhammad (International Journal of Engineering and Technology, 2018)
Machining process or metal cutting process is a main activity practised by small and medium metal enterprise by using HSS tool. This machining process is directed to produce the mass products, such as components of machine or another equipment’s, but often also the machining process is made inappropriately, or even in total false method, such as false selection of tool, thus the worn-out vastly, over cutting speed, thus surface is rougher, and etc. In this paper, the machinability on cast iron cutting is assessed (the material usually worked in small and medium metal industries), i.e.,  by making some experiment to obtain the most optimal cutting condition  (v, f ,and a) to have the short cutting time, big cutting volume, lower surface roughness  and longer  tool life.